A Novel Dual-Band “C+O” Structure Antenna - Tangyao Xie; Jianguo Yu; Ziheng Lin; Yao Li; Guodong Zhang; Zhen Yu (International Journal of Antennas and Propagation)
This article proposes a novel multiband antenna with “C + O” structure, which uses two classic circular letters and combines them. The antenna is suitable for wireless applications such as second generation (2G), third generation (3G), fourth generation (4G), WLAN, and Bluetooth. The antenna is based on the structural characteristics of the classic monopole antenna. It is a vertical quarter-wavelength antenna. The radiator of the antenna is mainly composed of letters, and the radiator is symmetrical along the feeder line. The antenna radiator is composed of “C + O” structure. The antenna uses a coplanar waveguide feeding method. After actual testing, the antenna covers two frequency bands: 1.82–2.66 GHz and 3.46–3.72 GHz. The center frequency points are 2.06 GHz and 3.68 GHz. The antenna uses FR-4 dielectric material, the relative dielectric constant of the dielectric plate is 4.4, and the actual size of the antenna is 15 × 15 × 1.6 mm³. The test and simulation have good consistency, which verifies that the proposed antenna meets the requirements of various wireless applications.